Women at altitude: sex-related physiological responses to exercise in hypoxia - Raberin, A.; Burtscher, J.; Citherlet, T. (Sports Medicine, 2024)
Sex differences in physiological responses to various stressors, including exercise, have been well documented. However, the specific impact of these differences on exposure to hypoxia, both at rest and during exercise, has remained underexplored. Many studies on the physiological responses to hypoxia have either excluded women or included only a limited number without analyzing sex-related differences. To address this gap, this comprehensive review conducted an extensive literature search to examine changes in physiological functions related to oxygen transport and consumption in hypoxic conditions. The review encompasses various aspects, including ventilatory responses, cardiovascular adjustments, hematological alterations, muscle metabolism shifts, and autonomic function modifications. Furthermore, it delves into the influence of sex hormones, which evolve throughout life, encompassing considerations related to the menstrual cycle and menopause. Among these physiological functions, the ventilatory response to exercise emerges as one of the most sex-sensitive factors that may modify reactions to hypoxia. While no significant sex-based differences were observed in cardiac hemodynamic changes during hypoxia, there is evidence of greater vascular reactivity in women, particularly at rest or when combined with exercise. Consequently, a diffusive mechanism appears to be implicated in sex-related variations in responses to hypoxia. Despite well-established sex disparities in hematological parameters, both acute and chronic hematological responses to hypoxia do not seem to differ significantly between sexes. However, it is important to note that these responses are sensitive to fluctuations in sex hormones, and further investigation is needed to elucidate the impact of the menstrual cycle and menopause on physiological responses to hypoxia.